Gel and porous polyethylene implants for anophthalmic cavity reconstruction-evaluation using the B scan ultrasound - Ferraz, Lucieni Cristina Barbarini [UNESP]; Schellini, Silvana Artioli [UNESP]; Hoyama, Erika [UNESP]; Wludarski, Sheila Lordelo [UNESP]; Padovani, Carlos Roberto [UNESP] (My University, 2009)
• Aim: To evaluate the host response of the gel and porous polyethylene implants in anophthalmic cavities using the B scan ultrasound. • Methods: Thirty-six white rabbits underwent unilateral enucleation with placement of gel or porous polyethylene spheres implants. The animals were submitted to clinical examination weekly and to ultrasound evaluation on 30, 60 and 90 days after surgery. • Results: All rabbits with gel polyethylene spheres, except one, showed implant extrusion probably because the gel spheres have hydrated and increased in volume. The B ultrasound of the gel polyethylene implant did not show vessels inside during the following period. Five animals (27. 8%) with porous polyethylene spheres presented implant extrusion after 30 days of surgery. According to B ultrasound, the porous polyethylene implant showed irregular and heterogeneous architecture and reflective peaks similar to vascularized tissues. • Conclusion: More studies are required to determine the ideal volume of gel polyethylene implant necessary to correct the diminished orbital content in the anophthalmic cavity. The B ultrasound effectiveness showed in this study for anophthalmic socket implants evaluation provided useful information for further in vivo studies and might substitute expensive methods of implants vascularization evaluation.
Keywords: Anophthalmic cavity; B ultrasound; Polyethylene implant; Rabbit